2015
DOI: 10.4238/2015.october.16.12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression analysis of WAG-1 in the pistillody line of common wheat

Abstract: ABSTRACT. Wheat WAG-1 is a C-class MADS-box gene, which is orthologous to AGAMOUS in Arabidopsis. In this study, we report the cloning, characterization, and expression patterns of WAG-1 in the pistillody mutant HTS-1 and its sib-line CSTP. The cDNA of WAG-1 was found to be 765 bp in length, which was equal to the length of its open reading frame, encoding 254 amino acids. The location of WAG-1 revealed that it has three homologous genes from the short arm of chromosome 1A, 1B, and 1D. Their genomic sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The AG-like gene subfamily includes members involved in the speci cation of stamen, carpel and ovule. Phylogenetic analysis showed that PfAG5 groups into AG-like clade in MADS-box genes of other plants, and is homologous to the A. tauschii AG-type genes as WAG-2f and WAG-2g [27], and Triticum aestivum TaAGL39 [28]. Overexpression of AGL79 in Arabidopsis result in the narrow leaf shape, fewer number of leaves and early owering [29], which is consistent with observed phenotypes of PfAG5 transgenic Arabidopsis plants in the current study ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The AG-like gene subfamily includes members involved in the speci cation of stamen, carpel and ovule. Phylogenetic analysis showed that PfAG5 groups into AG-like clade in MADS-box genes of other plants, and is homologous to the A. tauschii AG-type genes as WAG-2f and WAG-2g [27], and Triticum aestivum TaAGL39 [28]. Overexpression of AGL79 in Arabidopsis result in the narrow leaf shape, fewer number of leaves and early owering [29], which is consistent with observed phenotypes of PfAG5 transgenic Arabidopsis plants in the current study ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The AG-like gene subfamily includes members involved in the specification of stamen, carpel and ovule. Phylogenetic analysis showed that PfAG5 groups into AG-like clade in MADS-box genes of other plants, and is homologous to the A. tauschii AG-type genes as WAG-2f and WAG-2 g [27], and Triticum aestivum TaAGL39 [28]. Overexpression of AGL79 in Arabidopsis result in the narrow leaf shape, fewer number of leaves and early flowering [29], which are consistent with the phenotypes of PfAG5 transgenic Arabidopsis plants.…”
Section: Discussionsupporting
confidence: 64%
“…Transcription factors play an important role in regulating the development of plants. Some previous studies have reported that MADS-box [9,14,16,17,26,27,28] and DROOPING LEAF gene of YABBY family [6,15,16] associated with the development of wheat pistillody-stamen. We identify MADS-box and YABBY transcription factors from wheat flower substructure tissues (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of the TaEPFL1 gene in Arabidopsis caused shortened filaments and pedicels, which might induce stamens transformation into pistils or pistil-like structures in wheat [13]. Furthermore, some transcription factors of MADS-box and DROOPING LEAF gene of YABBY family have been considered to regulate in the development of wheat pistillody-stamen [6,9,[14][15][16][17][18]. The expression pattern analysis indicate that TaDL1, TaDL2, and…”
mentioning
confidence: 99%